PENGARUH MEDAN MAGNET SOLENOIDA DAN PERENDAMAN AIR MAGNETISASI TERHADAP BENIH KACANG KEDELAI ( Glicyne max (L) Merril) KADALUARSA VARIETAS TANGGAMUS - Yuhelsa Putra; Tubagus Bahtiar Rusbana; Livio Agung Dharmesta (Jurnal Agroekoteknologi, 2015)
The study aims to determine the effect of the magnetic field strength and the duration of magnetized water on germination of 2 year old Tanggamus of expired soybean seeds. The study was carried out in a closed room with the temperature used was 16°C-20°C in Desember 2015 to January 2016. The study was compiled using a completely randomized factorial design with 2 factor. The first factor is the magnetic field strength which consist of 4 level M0 (the magnetic field strength of solenoid 0mT), M1 (the magnetic field strength of solenoid 1mT), M2 (the magnetic field strength of solenoid 2mT), M3 (the magnetic field strength of solenoid 3mT). The second factor is the duration of magnetized water which consists of 3 level T1 (the 18 hour duration of magnetized water), T2 (the 24 hour duration of magnetized water), T3 (the 36 hour duration of magnetized water). The treatment was repeated 3 times so that there are 36 units of observed variables experiment such as the germination age the potential of growth, the maximum speed of growth, the normal percentage of germination, the abnormal percentage of germination, the abnormal percentage of germination. The solenoid magnetic field treatment level 2 mT gave a very real influence on the parameters of the age of maximum growth potential, the growth rate, the percentage of normal seedliry of 6 month old and 2 year old expired soybean seeds. The treatments of soaking seeds with 24 hour duration of magnetized water produced the best developments on the 6 month old and 2 year old expired seeds even though there are differences in same of the best results in the observation parameter of both of the expired speeds. The best level treatment of 6 month old expired seed is the interaction of M2T2 level (the magnetic field strength 2mT and the duration of 24 hour magnetized water) which provided the best result to the parameter of maximum growth potential, percentage of normal germination, and percentage of abnormal germination. While the best level treatment of 2 year old expired seed is the interaction of M2T3 level (the magnetic field strength 2mT and the duration of 36 hour magnetized water) which provided the best result to the parameter of germination age, speed of growth and percentage normal germination.Key words : magnetized, solenoid, expiry, germination, soybean, seeds